Presumptive Haematomyelia Secondary to Warfarin Toxicosis in a Dog - Carlos Blanco; Meritxell Moral; Juan José Minguez; Valentina Lorenzo (Case Reports in Veterinary Medicine)
A 3-year-old male entire Boxer was presented for a 6-day history of progressive symmetric nonambulatory tetraparesis with diffuse spinal hyperesthesia. Eight days prior to admission, the dog ingested warfarin accidentally, exhibiting systemic clinical signs of intoxication 2 days later. Upon referral, the dog was nonambulatory with paretic thoracic limbs and plegia with absent nociception on pelvic limbs, spinal reflexes were decreased to absent in all four limbs, and urinary and faecal incontinence were noticed. Magnetic resonance imaging (MRI) of the cervical, thoracic, and lumbar regions of the vertebral column revealed intramedullary lesions extending from the first cervical segments to the conus medullaris consistent with extensive intramedullary haemorrhages. Despite management with vitamin K1 and physiotherapy, 6 weeks later, improvement was limited to thoracic limb motor function, and euthanasia was elected. This case reports an extensive presumptive haematomyelia with severe neurological deficits suspected to be secondary to warfarin intoxication in a dog.